Effects of single subanesthetic dose of oxycodone on pain and Th1/Th2 balance in patients after radical mastectomy - QU Na，ZHAO Xiaohong，NI Qiang (Zhongguo linchuang yanjiu)
Objective To compare the effects of oxycodone and fentanyl on postoperative pain relief，immune balance of T-helper cells（Th），and adverse reactions in radical mastectomy. Methods A total of 120 female patients whounderwent elective radical mastectomy at Shanghai Public Health Clinical Center between December 2021 and January2024 were selected for this study. They were randomly divided into two groups using a random number table：the observation group（oxycodone group）and the control group（fentanyl group），with 60 patients in each group. The combined intravenous-inhalation general anesthesia were performed in both groups. During anesthesia induction，the observation group received an intravenous injection of oxycodone hydrochloride（0.1 mg/kg），and the control group received an intravenous injection of fentanyl citrate（1.0 μg/kg）. Both groups received remifentanil for maintenance during surgery. Postoperative visual analog scale（VAS）scores，Th1 and Th2 levels were recorded at 1，6，12，24，and 48 hours post-surgery. Differences in VAS scores between the groups were analyzed using a difference -in-differences（DID）model，and repeated measurement ANOVA was used for Th1，Th2，and Th1/Th2 levels. A quintile group analysis was performed to explore the relationship between Th1/Th2 levels and the risk of postoperative pain. Adverse reactions in both groups were analyzed using log-binomial regression. Results （1）The postoperative VAS scores of both groups decreased with the prolongation of time（1 h→6 h→12 h→24 h→48 h）（P<0.05），and the VAS score of the observation group was lower than that of the control group at each time point after operation（P<0.05）.（2）The results of the DID model analysis showed significant differences in VAS scores based on group，time，and the group × time interaction（P<0.01）.（3）The postoperative Th1/Th2 ratio of the two groups increased in the intra-group effect analysis（time factor）. The observation group had a significantly better Th1/Th2 ratio at 1，6，12，24，and 48 hours post-surgery compared to the control group（inter-group principal effect analysis）. The Th1/Th2 ratio continued to show a significant improvement in the observation group over time compared to the control group （inter-group × time interaction）.（4）Logistic regression analysis revealed that different Th1/Th2 levels were independently associated with postoperative pain（P<0.01）.（5）Compared to the control group，the observation group had a significantly lower risk of overall adverse reactions（RR=0.342，95%CI：0.146-0.783，P<0.05）. Conclusion The use of oxycodone during radical mastectomy can enhance postoperative analgesia，promote Th1/Th2 immune balance，and reduce the incidence of adverse reactions compared to fentanyl.